Christine Barbara Grinham. (2nd February 2019) - Heywood, Emma; Newman, Julia; Sidenius, Katryn; Taylor, Anne; Webber, Sandra
Abstract : A dedicated vet who, from graduation to retirement, had the best interests of her patients and staff at heart. She loved the countryside and being outdoors, especially with her husband and their dogs.